Model Kepemimpinan Walikota Pekalongan Basyir Ahmad Syawie Di Kota Pekalongan (2005-2015) - Bahri, Rofiul; ., Fitriyah (Journal of Politic and Government Studies, 2018)
The Leadership Model is the key to the success of the Regional Head in leading. Leadership model can never be separated from the style of leadership practiced by the Head of Region. In the government organization, the role of leader is expected to be able to manage the various resources it has to achieve the goals or VISION, MISSION organization with style and model in accordance with the work environment and able to adapt to situation and condition of the organization.The research method used is qualitative approach with observation data collection techniques, interviews and documents. Informants in this research are Mayor, Secretary, Head of Bappeda, Chairman of NU, Chairman of Muhammadiyah, Chairman of Parliament and Chairman of Pecinta Batik Pekalongan.The results of this study indicate that the leadership style practiced by M. Basyri Ahmad Syawie is a style of democratic leadership. And the model of leadership using transformational leadership model. Leadership M. Basyir Ahmad Syawie can be successful, because in his leadership many achievements achieved by Pekalongan City. However, there are two factors inhibiting the leadership of M. Basyir Ahmad Syawie namely internal and external factors. The interernal factor comes from the old culture of bureaucracy and leadership personality. External factors come from supporting parties that overly intervene in bureaucratic affairs.Keywords: Leadership, Leadership Model